2019
DOI: 10.12669/pjms.35.5.133
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index before pregnancy and the amount of weight that should be gained during pregnancy: A cross-sectional study

Abstract: Objective: To investigate the adaptation of pregnant women to the recommended weight gain range according to body mass index (BMI) and to determine the factors affecting them. Methods: This cross-sectional study was performed in a university hospital’s obstetrics and gynecology unit (tertiary center) in Turkey. This study was conducted between March 2018 and August 2018 (6 months) in pregnant women. Pregnant women with chronic disease and receiving treatment during antenatal follow-up, with twin pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…A study found that the mean BMI of pregnant women was 24.84 ± 4.62 kg/m2, with 3.2% categorized as low weight, 52.6% as normal weight, 27.5% as overweight, and 16.7% as obese [14]. These findings provide insights into the diverse socioeconomic backgrounds of the study participants, which may influence various health outcomes, including musculoskeletal health during pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…A study found that the mean BMI of pregnant women was 24.84 ± 4.62 kg/m2, with 3.2% categorized as low weight, 52.6% as normal weight, 27.5% as overweight, and 16.7% as obese [14]. These findings provide insights into the diverse socioeconomic backgrounds of the study participants, which may influence various health outcomes, including musculoskeletal health during pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…Ozdilek R et al emphasized upon importance of pre-pregnancy counselling for weight loss as it directly affects weight gain during pregnancy and feto-maternal outcomes. 13 Most epidemiological studies regarding this association are mainly from Western countries with limited literature from Asian population. A systematic review by Goldstein reported higher pre pregnancy BMI in women from Western countries than eastern Asians.…”
Section: Discussionmentioning
confidence: 99%
“…22 Çalışmalar doğum sayısı arttıkça, kadınların kontrol edemeyeceği bir dizi risk faktörünün ortaya çıkabileceğini göstermektedir. 20,23 Ayrıca gebelikte anemi ve postpartum kanamalarla da ilişkili olabileceği vurgulanmaktadır. 24,25 Katılımcılar gebe olduklarını ortalama 5,67±2,53 gebelik haftasında öğrendiğini bildirdi.…”
Section: Introductionunclassified